Distribution of cold and temperate ice in glaciers on the Nordenskiold Land, Spitsbergen, from ground-based radio-echo sounding - Yu. Ya. Macheret; A. F. Glazovsky; I. I. Lavrentiev; I. O. Marchuk (Лëд и снег)
Data of ground-based radio-echo sounding of 16 glaciers located on the Nordenskiold Land, Spitsbergen, carried out in springs of 1999, 2007 and 2010–2013, allowed defining five glaciers as of the cold thermal type while other eleven ones were polythermal glaciers. In the last ones (polythermal) the average thickness of the upper layer of cold ice and the bottom layer of temperate ice was equal to 11-66 m and 15-96 m, respectively. The ratio of these thicknesses varies from 0.32 to 2.28, and the volume fraction of temperate ice in the total volume of the glaciers varies from 1 to 74% and changes from 0 to 50% in the ablation zone up to 80% in the accumulation zone. Thickness of cold ice was determined by measured delay time of radar reflections from cold-temperate surface (CTS) while thickness of temperate ice was derived as a difference between the total thickness of the glacier and the thickness of its cold ice. For interpretation of radar reflections from CTS we used the noticeable distinction in character of the radar reflections from the upper and lower thicknesses of glacier: absence of internal reflections (excluding reflections from buried crevasses and glacier wells) from upper cold ice layer and a great number of reflections of hyperbolic form from the lower layer related to strong scattering of radio waves by water inclusions in the temperate ice. According to the measurements, relative power of the radar reflections from CTS is by 5,5–14,2 dB smaller than those from the bedrock, that can be considered as an indicator of smaller water content at CTS; so, the repeated measurements of their relative power can be used for estimation of temporal changes in the water content at these boundaries. In layers of the temperate ice, the series of vertical hyperbolic reflections penetrating the cold ice down to CTS and further to the bedrock were detected. Such reflections are related to buried crevasses and/or the glacier wells and can serve as sources of the water permeating during the melt periods from the glacier surface down to CTS and bedrock and, thus, influencing on the ice viscosity and fluidity as well as on velocity of the bottom sliding in the polythermal glaciers. Repeated measurements of relative power of reflections from buried crevasses and wells can also be used to study processes of freezing them through and emptying during the period before start of the surface melting. Relation between volume of temperate ice and area of 16 studied glaciers was used to estimate the probability of existence of polythermal glaciers with a temperate ice core in all 202 glaciers in the Nordenskiold Land. 72 glaciers with areas exceeding 1.79 km2 may be referred to the polythermal type. The probable total volume of temperate ice in these glaciers amounts roughly to 10 km3, and with the 95% confidence it is within the interval from 8 to 33 km3. Almost 80% of the whole temperate ice may be concentrated in only five glaciers with area more than 17 km2, that makes up 2.5% of the total number of glaciers and about 30% of their total area. Data presented in this paper demonstrate more sophisticated pattern of the cold and temperate ice distribution within the glaciers than it was earlier known that should be taken into consideration when modeling and forecasting dynamics of the polythermal glaciers and investigating internal processes of the temperate ice formation in such glaciers.